Takayasu’s arteritis in pregnancy - Sawant, Rupali N.; Bhatiyani, Binti; Gaikwad, Pradip; Azad, Sara (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
We had the opportunity to manage a pregnant lady who presented for the first time at 34 weeks of amenorrhea with absent pulses in upper limbs on examination. She underwent Magnetic Resonance Angiography to confirm the diagnosis of Takayasu’s arteritis. Luckily she did not have complications of Takayasu’s such as hypertension, cardiac failure, neurological symptoms, visual disturbances. She proceeded to have a normal vaginal delivery after aggressive management which included a multidisciplinary team involving obstetrician, cardiologist, physician and rheumatologist.